Working capital policies and firm performance - Maizatul Ashikin, Abdul Karim (2014)
This study is conducted to examine the relationship between the working capital components (ACP, APP, ICP and CCC) and the working capital policies (AIP, CIP, AFP and CFP) with the firms’ performance (ROA, ROE and Tobin’s Q). This study takes place from 2008 until 2012 and was examined on six sectors listed in Bursa Malaysia which are the construction , consumer products, industrial products, plantations, properties and also trading and services. Ordinary least squares regression and fixed effect model have been used to estimate the relationship between variables. The results showed that different sector may give different results in determining the relationship between the working capital and the firms’ performance. Working capital components and firms’ performance is negatively related and it can be found in plantations, properties and trading and also services sectors. However, all the sectors showed that working capital policies will impact the firms’ performance except the plantations sector.